An Analysis of the Grade Twelfth Reading Curriculum in the Sultanate of Oman: Curriculum Alignment and Preparation for Academic reading at The University level - Rashid Hamed Nasib Al Azri (Universiti Sains Islam Malaysia, 2024)
Given the importance of English in all professions and as a global language, enhancing reading proficiency in English is one of the key objectives in the Omani education system. However, reading in English has been one of the major problems in the Omani setting especially among university students. Hence, the current study examined the Omani Grade Twelve EFL reading curriculum in terms of its alignment with the communicative approach as well as how the Omani Grade Twelve EFL reading curriculum prepares students for the academic reading skills required by universities. Data were collected via reviewing the reading tasks extracted from the Grade Twelve Engage With English (EWE) book, EWE course books (A+B), EWE Teacher's Books (A+B) and through classroom observations in the selected schools. This study factored in numerous dynamics such as Second Language Acquisition (SLA) theories and second language reading theories and their corresponding instructional approaches, types of learners' role, types of teachers' role, the emphasis on reading as the means to achieve the learning outcomes specified in the Omani Grade Twelve (EWE) EFL reading curriculum, types of passages and length, level of cognitive demands and level of lexical diversity in the reading passages in the EFL Grade Twelve Course book. The researcher utilised manifested content analysis for analysing the data of the current study. The findings regarding the SLA theories indicate that there is a misalignment between the communicative label of the Omani EFL Grade Twelve reading curriculum and its grounding theories. In addition, In addition, the findings on teachers' role indicate that the teacher primarily acts as a director rather than catalyst while the learners' role is designed to be primarily as an individual task rather than pair/group task. Regarding the preparation of grade twelfth students for academic reading in English at the university level, the grade twelfth curriculum does not fully train the learners on three types of major reading tasks. As for the cognitive demands, the grade twelfth reading curriculum trains students with reading tasks that require a high level of cognitive demands. The findings show that the grade twelfth reading curriculum trains the students to process texts in English at a grade level as the majority of reading passages are up to the grade level in terms of length of the passage, however, with the majority of passages being expository in nature with some narrative passages. The findings of the current study are important not only to the curriculum designers in Oman but also to other countries where the English language is a foreign language.